(untitled) (Journal of International Studies, 2024)
This article considers the nature of Turkish-Greek relations, focusing on the question of how these should be characterized. This is an important topic not only because there is a lack of a clear definition of the situation between the two countries in the literature, but also because providing a greater clarity of the issues about Turkish-Greek relations can assist in the long-term envisioning of a possible path that the two countries might take in the future. Employing a descriptive analysis, the article shows that a state of conflict rather than cooperation has determined the evolution of relations between Turkey and Greece. This sheds light on the intractable nature of the problems between the two countries, whether in Cyprus, the Aegean Sea, or the Eastern Mediterranean. The article concludes that Turkish-Greek relations are characterized by a historically grounded condition of fragile stability, with permanent tension and possible crisis prevailing, even if conflicts are frozen and war is not foreseen.